2020
DOI: 10.34172/jrip.2020.17
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and ultrastructural findings of hereditary nephritis; a 16-year single center survey in Iran

Abstract: Introduction: Hereditary nephritis is an umbrella term for a group of congenital childhood diseases including but not limited to Alport syndrome, thin basement membrane disease, and Fabry disease. Objectives: The purpose of this study was a clinicopathologic investigation of Alport syndrome, thin basement membrane disease, and Fabry disease with a focus on the role of electron microscopy and toluidine blue staining in diagnosis. Patients and Methods: In this cross-sectional study, we investigated kidney biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…The only available data and study from Iran is a recently published study from Shiraz University of Medical Sciences, which reported 22 (0.77%) HN patients among 2865 kidney biopsies in a 16-year survey. 18 The large difference between the results of these two studies can mainly be explained by the fact that our center, as the only available EM center in Tehran, is a highly selective referral center that receives more suspicious cases for the confirmation of HN and handles at least 30% more kidney biopsy samples (3884 in 12 vs. 2865 in 16 years) per year compared to their center.…”
Section: Discussionmentioning
confidence: 92%
“…The only available data and study from Iran is a recently published study from Shiraz University of Medical Sciences, which reported 22 (0.77%) HN patients among 2865 kidney biopsies in a 16-year survey. 18 The large difference between the results of these two studies can mainly be explained by the fact that our center, as the only available EM center in Tehran, is a highly selective referral center that receives more suspicious cases for the confirmation of HN and handles at least 30% more kidney biopsy samples (3884 in 12 vs. 2865 in 16 years) per year compared to their center.…”
Section: Discussionmentioning
confidence: 92%